THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND LEADERSHIP QUALITIES IN STUDENTS - Романовський, Олександр Георгійович; Підбуцька, Ніна Вікторівна; Книш, Анастасія Євгенівна; Штученко, Ірина Євгенівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
In this article, the main approaches concerning the problem of leadership traits formation as studied in both national and foreign literature are viewed. There are given results of research on leadership traits in students at technical specialties and humanities in the course of their training at a higher education institution in their connection with emotive intellect. The peculiarities of leadership traits in the tested groups with different level of emotive intellect, as well as a connection between leadership traits and emotive intellect are determined. The highest indicators according to the results of the research are demonstrated by a group of students of technical specialties with a high level of emotional intelligence, which indicates the ability to manage their emotions and behavior, the ability to solve problems. They demonstrate a high level of organizational skills, ability to work with a group. Their actions are aimed at achieving goals. The lowest rates according to the results of the study were found in a group of students of humanities with a low level of emotional intelligence. In difficult situations, it is difficult for them to find a way out. They do not know how to control the work of their comrades, to find common ground with people. The relationship between emotional intelligence and leadership skills in students of technical and humanities has been studied. A group of technical students with a high level of emotional intelligence found positive correlations between emotional intelligence and all scales of leadership qualities. There are no correlations between emotional intelligence and leadership qualities in the group of humanities students with a low level of emotional intelligence. In other groups of students, certain correlations have been established between emotional intelligence and leadership qualities.